Dr. Sergio Moreno Limón: Algunos Datos Biográficos - Salcedo Martínez, Sergio Manuel; Alvarado Vázquez, Marco Antonio (Revista Planta, 2025)
Espacio dónde se plasman algunos datos biográficos sobre el Dr. Sergio Moreno Limón.